Strategi Guru dalam Membentuk Green Behavior pada Siswa Kelas IV Sekolah Dasar Negeri Sarakan III Kabupaten Tangerang - Irma Agustin; Mawardi Mawardi; Ferry Perdiansyah (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study aims to analyze the strategies applied by teachers in shaping students' green behavior in grade IV of SDN Sarakan III, Sepatan District, Tangerang Regency. The approach used is descriptive qualitative. The research subjects include grade IV teachers, students, and the school principal. Data collection was carried out through observation, interviews, and document studies. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The research results show that teachers implement five main strategies, namely: (1) designing learning according to the objectives and characteristics of students; (2) encouraging active student participation; (3) presenting material contextually; (4) using Project Based Learning (PjBL) methods and the Contextual Teaching and Learning (CTL) approach; and (5) habituating environmentally caring behavior in everyday school life. The implementation of students' green behavior has been observed in the aspects of knowledge, attitude, and action, although consistency still needs to be improved, especially due to limited school facilities and differences in students' levels of awareness.